Bandgap-tunable cesium lead halide perovskites with high thermal stability for efficient solar cells - Sutton, R; Eperon, G; Miranda, L; Parrott, E; Kamino, B; Patel, J; Hörantner, M; Johnston, M; Haghighirad, A; Moore, D; Snaith, H (2016)
Highest reported efficiency cesium lead halide perovskite solar cells are realized by tuning the bandgap and stabilizing the black perovskite phase at lower temperatures. CsPbI2Br is employed in a planar architecture device resulting in 9.8% power conversion efficiency and over 5% stabilized power output. Offering substantially enhanced thermal stability over their organic based counterparts, these results show that all-inorganic perovskites can represent a promising next step for photovoltaic materials.